Risk Evaluation of Musculoskeletal Disorders (MSDs) at the Outpatient Registration Centre: A Review of Work Postures with the Rapid Office Strain Assessment (ROSA) Method - Golo, Zefan Adiputra; Lestari, Sri; Hapsari, Meilinda Asrining; Jannaty, Manzilina Hani Baity; Ningrum, Defi Dwi Cahya (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
Ergonomic conditions at the Outpatient Registration Centre (TPPRJ) of RSUD dr. Gondo Suwarno are inadequate, which causes officers to experience musculoskeletal complaints due to inappropriate work postures. This study aims to evaluate ergonomic aspects at TPPRJ using the Rapid Office Strain Assessment (ROSA) method to assess officer work postures. The research was conducted with a qualitative descriptive approach through observation, interviews, and anthropometric measurements. The results showed that work facilities, such as desks, chairs, as well as the position of monitors and other devices, did not match the officer's body dimensions, which resulted in a ROSA score of 9, indicating a high risk of musculoskeletal disorders. These findings highlight the importance of adjusting work facilities according to ergonomic standards and training in correct posture to improve officer comfort and health, thereby supporting improved quality of health services at TPPRJ.